Дослідження можливості проведення invariant subspace атаки на енергоефективний алгоритм Midori - Наумов, О.; Руженцев, В. І. (ХНУРЕ, 2019)
In the past few years, lightweight cryptography has become a popular research discipline with a number of ciphers and hash functions proposed. The designers’ focus has been predominantly to minimize the hardware area, while other goals such as low latency have been addressed rather recently only. However, the optimization goal of low energy for block cipher design has not been explicitly addressed so far. At the same time, it is a crucial measure of goodness for an algorithm. Indeed, a cipher optimized with respect to energy has wide applications, especially in constrained environments running on a tight power budget such as Internet of Things.
Keywords: Midori; lightweight блоковий шифр; AES; слабкі ключі; бітові перестановки; S-box.